Stoking the Fires of Pre-service Educators through Aboriginal and Torres Strait Islander Ways of Learning - Sharon Louth; Keane Wheeler; Romina Jamieson-Proctor; Tracey Sanderson (Universitas Majalengka, 2023)
Great emphasis has been placed on embedding Indigenous knowledges and perspectives in western-based education systems and pedagogical practices. This study discusses the results of a four-month program for pre-service teachers that targeted best-practice Aboriginal and Torres Strait Islander pedagogy.Â The program challenged existing notions of western-based teaching and learning through innovative approaches to the design of learning. Specifically, the program has been underpinned by the 8 Ways Aboriginal Pedagogical Framework which focuses on interconnected learning experiences which have been developed through Aboriginal systems, protocols, values and processes. The program embedded authentic practices aimed at empowering pre-service teachers. The research design explored four dimensions of empowerment relating to embedding Aboriginal and Torres Strait Islander perspectives: knowledge, understanding, perceptions and attitudes. Quantitative survey data was gathered pre and post program and paired samples t-tests were conducted and found all four dimensions of empowerment improved significantly following the program (p < 0.05). The results of this study demonstrate the effectiveness of teaching, learning and assessing through the lens of the 8 Ways Aboriginal Pedagogical framework to increase teacher agency to become more culturally responsive educators.